1992
DOI: 10.1007/bf00009540
|View full text |Cite
|
Sign up to set email alerts
|

Soil phosphorus status, pH and the manganese nutrition of wheat

Abstract: A pot experiment was carried out in order to test the hypothesis that manganese nutrition of wheat was dependent on the phosphorus status of soil as well as on its pH and manganese status. An arable mineral soil whose lime and phosphorus status had been massively adjusted more than 18 years previously was compared with identical soil not so adjusted. Wheat plants were grown to maturity in these soils. Analyses were carried out on both soil and plant samples at intervals. Data for soil pH, soil solution concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 9 publications
2
19
0
Order By: Relevance
“…This property is likely due to their tendency to transform into other less bioavailable forms, such as homo aggregation or hetero aggregation/precipitation into insoluble complexes with other soil constituents, such as phosphate [42]. Indeed, a role for P in inhibiting Mn accumulation in wheat has been noted [43], which may be applicable in the present study, given the relatively high level of added P in the soil.…”
Section: Shoot Uptake Of Manganese Is Inhibited By Soil-applied Nano Mnmentioning
confidence: 72%
“…This property is likely due to their tendency to transform into other less bioavailable forms, such as homo aggregation or hetero aggregation/precipitation into insoluble complexes with other soil constituents, such as phosphate [42]. Indeed, a role for P in inhibiting Mn accumulation in wheat has been noted [43], which may be applicable in the present study, given the relatively high level of added P in the soil.…”
Section: Shoot Uptake Of Manganese Is Inhibited By Soil-applied Nano Mnmentioning
confidence: 72%
“…In contrast to Si, it is uncertain if increased phosphorus (P) supply improves a plant's tolerance to high Mn. High soil P decreased Mn in wheat ( Triticum aestivum ) shoots (Neilsen et al ., ) but not in perennial ryegrass ( Lolium perenne ) (Le Mare, ) or soybean ( Glycine max ) (Nogueira et al ., ). Rosas et al .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to Si, it is uncertain if increased phosphorus (P) supply improves a plant's tolerance to high Mn. High soil P decreased Mn in wheat (Triticum aestivum) shoots (Neilsen et al, 1992) but not in perennial ryegrass (Lolium perenne) (Le Mare, 1977) or soybean (Glycine max) (Nogueira et al, 2007). Rosas et al (2011) reported that high P ameliorates Mn toxicity in perennial ryegrass and white clover (Trifolium repens) despite increased Mn in roots and shoots.…”
Section: Introductionmentioning
confidence: 99%
“…A glasshouse experiment was designed to compare Mn concentrations in soil solutions and the Mn nutrition of wheat plants in soils which had received different amounts of both P and lime some 18 years previously (Neilsen et al, 1992). These treatments had significantly altered both P status and soil pH.…”
Section: Intensity Of Use Of Agricultural Land and Future Pressuresmentioning
confidence: 99%
“…However, the results for high P soils could not be related to soil solution composition. Neilsen et al (1992) suggested that high soil P resulted in elevated plant P that interfered in the uptake and/or translocation of Mn, rather than by a direct effect of soil chemistry on Mn availability.…”
Section: Intensity Of Use Of Agricultural Land and Future Pressuresmentioning
confidence: 99%